The Role of Digital Promotion in Mediating the Effects of Influencers, Social Media, and Tourism Events on the Competitiveness of Agrotourism (A Case Study of Sangkanika Edugarden Agrotourism) - Fahmi Naha Bafil’Amali; Wachdijono; Akhmad Jaeroni (Indonesian Journal of Advanced Research, 2026)
Promotion in the tourism sector plays a crucial role in introducing destinations, building a positive image, and increasing tourists' intention to visit. However, many tourism destination managers have yet to implement promotional strategies optimally. This study aims to examine the effects of influencers, social media, and tourism events on digital promotion and their implications for the competitiveness of Sangkanika Edugarden Agrotourism. A quantitative research design was employed using purposive sampling to select 132 respondents who had visited Sangkanika Edugarden Agrotourism. Data were collected through a structured questionnaire using a five-point Likert scale during April–May 2026 and analyzed using path analysis with IBM SPSS Statistics 26. The findings indicate that influencers, social media, and tourism events have positive and significant effects on digital promotion. Furthermore, digital promotion has a positive and significant effect on destination competitiveness. The results also reveal that digital promotion mediates the effects of influencers, social media, and tourism events on competitiveness. These findings suggest that enhancing destination competitiveness depends not only on the effective utilization of influencers, social media, and tourism events but also on the ability to integrate these three marketing strategies through effective digital promotion. This study contributes to the development of digital marketing strategies for agrotourism destinations.